Design Rationale and Preclinical Evaluation of the HeartMate 3 Left Ventricular Assist System for Hemocompatibility. Issue 4 (July 2016) - Bourque, Kevin; Cotter, Christopher; Dague, Charles; Harjes, Daniel; Dur, Onur; Duhamel, Julien; Spink, Kaitlyn; Walsh, Kelly; Burke, Edward
Abstract : The HeartMate 3 (HM3) left ventricular assist device (LVAD) is designed to support advanced heart failure patients. This centrifugal flow pump has a magnetically levitated rotor, artificial pulse, textured blood-contacting surfaces, optimized fluid dynamics, large blood-flow gaps, and low shear stress. Preclinical tests were conducted to assess hemocompatibility. A computational fluid dynamics (CFD) model guided design for low shear stress and sufficient washing. Hemolysis testing was conducted on six pumps. Plasma-free hemoglobin (PfHb) and modified index of hemolysis (MIH) were compared with HeartMate II (HMII). CFD showed secondary flow path residence times between 27 and 798 min, comparable with main flow residence times between 118 and 587 min; HM3 vs . HMII shear stress exposure above 150 Pa was 3.3 vs. 11 mm 3 within the pump volume and 134 vs. 604 mm 2 on surfaces. In in vitro hemolysis tests at 2, 5, and 10 L/min, average pfHb 6 hours after test initiation was 58, 74, and 157 mg/dl, compared with 112, 123, and 353 mg/dl for HMII. The HM3/HMII ratio of average MIH at 2, 5, and 10 L/min was 0.29, 0.36, and 0.22. Eight 60 day bovine implants were tested with average flow rates from 5.6 to 6.4 L/min with no device failures, thrombosis, or hemolysis. Results support advancing HM3 to clinical trials.